PRODUCT RECALL: A COMMENTARY ON RISING INCIDENCES - Chawla, Viney; Singh, Manish Pal; Kumar, Manish (Universal Journal of Pharmaceutical Research, 2016)
There has been an increasing trend in the number of prescribed and over-the-counter drug recall over the last few years. The recall is usually due to company’s discovery, customer’s complaint or Food and Drug Administration (FDA) observation. The process of recall involves a planned specific course of action, which addresses the depth of recall, need for public warning, and the extent of effectiveness checks for the recall. The FDA review and/or recommend changes to the firm’s recall strategy, as appropriate. The critical recall information list includes the identity of the product; summary of the failure; amount of product produced in the distribution chain and direct account. Product recalls clashes thousands of companies every year affecting: sales, testing customer relationships and disrupting supply chains. Drug recall is incubus for pharmaceutical companies. It effects the reputation of the company. The reason for the recall can be divided into two categories: manufacturing related and safety/efficacy related. It is essential to follow all the guidelines related to drug development and manufacturing procedure to minimize drug recall. Peer Review History: Article received on- 28 September 2016; Revised on- 3 November; Accepted on- 11 December; Available online 15 January 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Luisetto Mauro , AUSL PC, Piacenza Area, Italy, M.Luisetto@ausl.pc.it Dr. Mahmoud S. Abdallah , University of Sadat city, Egypt, dr_samy777@yahoo.com